2022
DOI: 10.3390/s22041348
|View full text |Cite
|
Sign up to set email alerts
|

Non-Contact Smart Sensing of Physical Activities during Quarantine Period Using SDR Technology

Abstract: The global pandemic of the coronavirus disease (COVID-19) is dramatically changing the lives of humans and results in limitation of activities, especially physical activities, which lead to various health issues such as cardiovascular, diabetes, and gout. Physical activities are often viewed as a double-edged sword. On the one hand, it offers enormous health benefits; on the other hand, it can cause irreparable damage to health. Falls during physical activities are a significant cause of fatal and non-fatal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The possible tracker devices used in this study were Fitbit, Apple Watch, Polar, Garmin, and Nike. These wireless devices are a useful tool for continuously monitoring physical activities and may assist patients suffering from chronic pathologies [55]. Thus, Fitbit, Apple Watch, and Garmin have been validated to examine heart rate and energy expenditure at different exercise intensities [56].…”
Section: Discussionmentioning
confidence: 99%
“…The possible tracker devices used in this study were Fitbit, Apple Watch, Polar, Garmin, and Nike. These wireless devices are a useful tool for continuously monitoring physical activities and may assist patients suffering from chronic pathologies [55]. Thus, Fitbit, Apple Watch, and Garmin have been validated to examine heart rate and energy expenditure at different exercise intensities [56].…”
Section: Discussionmentioning
confidence: 99%
“…First, the non-significant change may indicate the complexity of the impact of the COVID-19 pandemic on overall physical activity time, and there are different levels of physical activity, which include sedentary, light physical activity, and MVPA. Light physical activity with low exertion may increase during the COVID-19 pandemic, and Wilms et al (2022) proposed that the lockdown restrictions cause an increase in low MET activities, such as sedentary behavior (Janssen et al, 2020;Wilms et al, 2022), or increase in housework due to the long period of confinement (Wunsch et al, 2022). Meanwhile, some studies suggested a decrease in MVPA time for individuals during the COVID-19 pandemic (Janssen et al, 2020;Zinner et al, 2020;da Silva Santos et al, 2021), which is consistent with our final findings that MVPA time changed during the COVID-19 pandemic and people spent less time exercising, leading to a decrease in MVPA time, and Ugolini et al (2021) also suggested that many outdoor leisure activity places were completely closed or restricted, which could reduce people's MVPA time (Karuc et al, 2020).…”
Section: Physical Activitymentioning
confidence: 99%
“…In the period of early COVID-19, it was estimated that 2.6 billion people (Van Hoof, 2020 ) were in lockdown or quarantine for an average of 35.38 days in 49 countries (Atalan, 2020 ). Lockdown slowed down the spread of the coronavirus (Lau et al, 2020 ), but it influenced public health in both physical health (Werneck and Carvalho, 2020 ; Amerio et al, 2021 ; Jurecka et al, 2021 ; Knowles et al, 2021 ; Pensgaard et al, 2021 ; Jia et al, 2022 ) and mental health (McTiernan et al, 2019 ; Chandrasekaran and Ganesan, 2021 ; Khan et al, 2022 ). The most direct impact of COVID-19 on people was the changes in physical activity, which was reduced due to remote work or study (Bu et al, 2021 ) or the closure of outdoor activity areas (Ugolini et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Khan M.B. et al developed a non-contact smart sensing platform using software-defined radio technology to monitor physical activities during quarantine [ 1 ]. The platform is intelligent, portable, and multi-functional.…”
mentioning
confidence: 99%